2014
DOI: 10.1097/ijg.0b013e318285fd95
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Steady-state PERG in Early Glaucoma

Abstract: Purpose Previous studies have shown that the onset of high-contrast, fast reversing patterned stimuli induces rapid blood flow increase in retinal vessels in association with slow changes of the steady-state PERG signal. We tested the hypothesis that adaptive PERG changes of normal controls (NC) differed from those of glaucoma suspects (GS) and patients with early manifest glaucoma (EMG). Methods Subjects were 42 GS (SAP MD −0.89 ±1.8 dB), 22 EMG (MD −2.12 ±2.4 dB) with visual acuity of ≥20/20 and 16 age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…11 PERG adaptation provides specific physiological information on RGC function, 11,12 as it is selectively altered in diseases such as glaucoma 31 and optic neuritis. 21 To explore the response dynamic range and intrinsic variability over a wide range of conditions relevant to clinical application, we investigated the PERGx method in different groups of subjects including younger normal controls, older normal controls, open-angle glaucoma patients with modest visual field defects, and NAION patients with severe visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…11 PERG adaptation provides specific physiological information on RGC function, 11,12 as it is selectively altered in diseases such as glaucoma 31 and optic neuritis. 21 To explore the response dynamic range and intrinsic variability over a wide range of conditions relevant to clinical application, we investigated the PERGx method in different groups of subjects including younger normal controls, older normal controls, open-angle glaucoma patients with modest visual field defects, and NAION patients with severe visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…Phase consistency describes the SD of these measurements. A low phase consistency indicates a failure of the RGCs to adapt to the large energy demand of an ss‐PERG stimulus, leading to different phases as testing time goes on . This difference in phase consistency is demonstrated in Figures c,d.…”
Section: Discussionmentioning
confidence: 96%
“…The PERG test depends on the integrity of the retinal ganglion cells, and thus, parameters may be altered even before VF defects appear in patients with glaucoma. Previous studies have found abnormal PERG values in patients with glaucoma suspect and ocular hypertension without optic nerve or VF changes . The PERG test represents a well‐established surrogate measure of the function of retinal ganglion cells in glaucoma with a good repeatability .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…15,16,19 This may be due to the increased frequency of stimulus presentation, which results in a higher level of neural activity and, thus, increased metabolic stress. 31,32 Conventional tr PERG tr recordings show that P50 and N95 amplitudes are similarly affected in glaucoma patients, but the amplitude of the PERG SS is much more affected. 16 The overlap generation mechanism developed in this study explains this observation quite easily since P50 and N95 amplitudes contribute to the overall SS amplitude, and each tr peak reduction would result in even greater reduction in the overall SS amplitude.…”
Section: Discussionmentioning
confidence: 99%